2007
DOI: 10.1103/physrevd.76.056002
|View full text |Cite
|
Sign up to set email alerts
|

Possible experimental signatures at the CERN LHC of strongly interacting electroweak symmetry breaking

Abstract: If electro-weak symmetry is broken by a new strongly interacting sector, new physics will probably manifest itself in gauge boson scattering at the LHC. The relevant dynamics is well described in terms of an effective lagrangian. We discuss the probable size of the coefficients of the relevant operators under a combination of model-independent constraints and reasonable assumptions based on two models of the strongly interacting sector. We compare these values with LHC sensitivity and argue that they will be t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 54 publications
(57 reference statements)
0
20
0
Order By: Relevance
“…Due to the equivalence theorem this scattering is mapped directly into the pion-pion scattering of the underlying strongly coupled gauge theory driving the breaking of the electroweak theory. A similar analysis has been performed in [29]. We have shown that there are regions in the parameters space of these models, allowed by the electroweak precision data, according to which tree-level unitarity is delayed up to around 3-4 TeV without the inclusion of any sub-TeV resonances.…”
mentioning
confidence: 59%
“…Due to the equivalence theorem this scattering is mapped directly into the pion-pion scattering of the underlying strongly coupled gauge theory driving the breaking of the electroweak theory. A similar analysis has been performed in [29]. We have shown that there are regions in the parameters space of these models, allowed by the electroweak precision data, according to which tree-level unitarity is delayed up to around 3-4 TeV without the inclusion of any sub-TeV resonances.…”
mentioning
confidence: 59%
“…Bounds on the dimension-4 parameter in the ChL lagrangian compatible with precision electroweak constraints have been obtained in [7]. On Fig.…”
Section: Electroweak Constraints On the Chl Paramètersmentioning
confidence: 99%
“…The size of the coefficients OE4,OE5, describing the relevant dynamics of VBS at high energy in the effective ChL description can be given bounds by reasonable assumptions based on different models of the strongly interacting sector, as discussed in [7], and model-independent constraints as discussed in this section. In [7] the values are compared with LHC sensitivity and they seem to faH in the region where LHC is not sensible to this type of processes.…”
Section: Electroweak Constraints On the Chl Paramètersmentioning
confidence: 99%
See 2 more Smart Citations